(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Today, interest in using innovative technologies and interactive methods in the educational process is becoming more and more widespread. The use of such methods increases the effectiveness of education and increases the motivation of students to study. Innovation is to introduce and create something new. Therefore, innovation is the use of a form of work aimed at increasing the effectiveness of the educational process based on innovations, not on the basis of the same templates as in traditional education.